Lactobacillus rhamnosus CNCMI-4317 Modulates Fiaf/Angptl4 in Intestinal Epithelial Cells and Circulating Level in Mice - Jacouton, Elsa; Mach, Núria; Cadiou, Julie; Lapaque, Nicolas; Clément, Karine; Doré, Joël; van Hylckama Vlieg, Johan E. T.; Smokvina, Tamara; Blottière, Hervé M (PloS one, 2015)
Identification of new targets for metabolic diseases treatment or prevention is required. In this context, FIAF/ANGPTL4 appears as a crucial regulator of energy homeostasis. Lactobacilli are often considered to display beneficial effect for their hosts, acting on different regulatory pathways. The aim of the present work was to study the effect of several lactobacilli strains on Fiaf gene expression in human intestinal epithelial cells (IECs) and on mice tissues to decipher the underlying mechanisms. Nineteen lactobacilli strains have been tested on HT-29 human intestinal epithelial cells for their ability to regulate Fiaf gene expression by RT-qPCR. In order to determine regulated pathways, we analysed the whole genome transcriptome of IECs. We then validated in vivo bacterial effects using C57BL/6 mono-colonized mice fed with normal chow. We identified one strain (Lactobacillus rhamnosus CNCMI-4317) that modulated Fiaf expression in IECs. This regulation relied potentially on bacterial surface-exposed molecules and seemed to be PPAR-γ independent but PPAR-α dependent. Transcriptome functional analysis revealed that multiple pathways including cellular function and maintenance, lymphoid tissue structure and development, as well as lipid metabolism were regulated by this strain. The regulation of immune system and lipid and carbohydrate metabolism was also confirmed by overrepresentation of Gene Ontology terms analysis. In vivo, circulating FIAF protein was increased by the strain but this phenomenon was not correlated with modulation Fiaf expression in tissues (except a trend in distal small intestine). We showed that Lactobacillus rhamnosus CNCMI-4317 induced Fiaf expression in human IECs, and increased circulating FIAF protein level in mice. Moreover, this effect was accompanied by transcriptome modulation of several pathways including immune response and metabolism in vitro.